Machine learning : proceedings of the Twelfth International Conference on Machine Learning, Tahoe City, California, July 9-12, 1995 - Prieditis, Armand; Russell, Stuart J. (Stuart Jonathan), 1962- (Morgan Kaufmann Publishers, 1995)
Machine Learning Proceedings 1995.